Diorama lessicale d’un volgarizzatore dugentesco: il caso dei «Fiori di filosafi» (Carte Romanze, 2024)
The essay studies, through a series of examples, the lexicon of the Fiori e vita di filosafi e d’altri savi e d’imperadori, a Florentine translation from the early 1270s of some passages from the Flores historiarum by Adam of Clermont, compendium of the Speculum historiale by Vincent of Beauvais. On the one hand, the way of translating is examined, both from a stylistic point of view and in relation to the implicit communal ideology of the translator; on the other hand, a series of terms are proposed that are relevant for semantic aspects or because the Fiori di filosafi represent the first attestation in the history of the Italian language.